2022
DOI: 10.3390/cells11050764
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neurogenesis under Control of the Circadian System

Abstract: The mammalian circadian system is a hierarchically organized system, which controls a 24-h periodicity in a wide variety of body and brain functions and physiological processes. There is increasing evidence that the circadian system modulates the complex multistep process of adult neurogenesis, which is crucial for brain plasticity. This modulatory effect may be exercised via rhythmic systemic factors including neurotransmitters, hormones and neurotrophic factors as well as rhythmic behavior and physiology or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 213 publications
(296 reference statements)
0
16
0
1
Order By: Relevance
“…The cellular substrate for hippocampal learning and memory is neuroplasticity. Structural hippocampal plasticity is provided by changes in spine formation and by adult neurogenesis in the subgranular zone (SGZ) of the DG [ 127 , 128 , 129 ] which is strongly influenced by the circadian system [ 130 ]. We have shown that adult neurogenesis is affected in BMAL1-deficient mice [ 59 , 131 , 132 ].…”
Section: The Role Of Light and The Circadian Clock For Rhythmic Brain...mentioning
confidence: 99%
“…The cellular substrate for hippocampal learning and memory is neuroplasticity. Structural hippocampal plasticity is provided by changes in spine formation and by adult neurogenesis in the subgranular zone (SGZ) of the DG [ 127 , 128 , 129 ] which is strongly influenced by the circadian system [ 130 ]. We have shown that adult neurogenesis is affected in BMAL1-deficient mice [ 59 , 131 , 132 ].…”
Section: The Role Of Light and The Circadian Clock For Rhythmic Brain...mentioning
confidence: 99%
“…Активность гиппокампа опосредует связь между циркадными ритмами и состоянием памяти Ali, von Gall, 2022). Успешное разделение паттернов эмоциональных воспоминаний связано с тета-диапазоном в гиппокампе, тогда как ошибочное различение эмоциональных стимулов сопровождается усилением мощности альфа-диапазона (Zheng et al, 2019).…”
Section: гиппокамп через призму функциональной нейровизуализацииunclassified
“…Specifically, C3H mice with functional MT1/MT2 receptors show a time-of-day-dependent fluctuation in the number of proliferation neuronal stem/progenitor cells in contrast to the MT1/MT2 double KO mice ( Fredrich et al, 2017 ). Additional promoting effects of melatonin on adult neurogenesis such as antioxidative activity and enhanced expression of neurotrophic factors are suggested (reviewed in Ali and von Gall, 2022 ).…”
Section: Introductionmentioning
confidence: 99%